Evaluation of the performance of briquettes as potential feed material to the rotary kiln electric furnace at Barro Alto, Brazil - Naude, Natasia (University of Pretoria, 2025)
Dissertation (MEng (Metallurgical Engineering))--University of Pretoria, 2025.